2006
DOI: 10.1179/146532806x107511
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry muffin syndrome owing to congenital rubella: case report

Abstract: A case of congenital rubella is reported in a 22-day-old boy presenting with a 'blueberry muffin' rash. Late-onset blueberry muffin syndrome following congenital rubella is very rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…There were 19 articles that met the inclusion criteria and contained sufficient data available for review. Of these, nine were based on catheterization data alone (Rowe,1963; Emmanouilides et al,1964; Venables,1965; Sperling and Verska,1966; Hastreiter et al,1967; Celermajer et al,1969; Lie et al,1970; Kher et al,1980; Gorenflo et al,2002), nine on echocardiographic data alone (Janner,1991; Robinson et al,1994; Bullens et al,2000; St John and Benjamin,2000; Agarwal et al,2001; Banerji et al,2005; Koklu et al,2006; Wui et al,2006; Plotinsky et al,2007), and one on both catheterization and echocardiographic data (Moore and Mullins,1986) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were 19 articles that met the inclusion criteria and contained sufficient data available for review. Of these, nine were based on catheterization data alone (Rowe,1963; Emmanouilides et al,1964; Venables,1965; Sperling and Verska,1966; Hastreiter et al,1967; Celermajer et al,1969; Lie et al,1970; Kher et al,1980; Gorenflo et al,2002), nine on echocardiographic data alone (Janner,1991; Robinson et al,1994; Bullens et al,2000; St John and Benjamin,2000; Agarwal et al,2001; Banerji et al,2005; Koklu et al,2006; Wui et al,2006; Plotinsky et al,2007), and one on both catheterization and echocardiographic data (Moore and Mullins,1986) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, if rubella is acquired during the first 10 weeks of pregnancy, the fetus is at high risk of congenital rubella syndrome (CRS) [1], with manifestations ranging from deafness, cardiac disease, and cognitive impairment to miscarriage and fetal death [2][3][4]. The incidence of CRS in Canada is rare, with an average of 0.69 cases per year between 1998 and 2010 [5].…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, the rashes were present at birth and disappeared completely by 10th day. Koklu et al [10] reported late-onset blueberry muffin rash following congenital rubella.…”
Section: Discussionmentioning
confidence: 99%